Freedom at Risk : The Kidnapping of Free Blacks in America, 1780-1865 - Wilson, Carol, 1962- (Book collections on Project MUSE., 2009)
Kidnapping was perhaps the greatest fear of free blacks in pre-Civil War America. Though they may have descended from generations of free-born people or worked to purchase their freedom, free blacks were not able to enjoy the privileges and opportunities of white Americans. They lived with the constant threat of kidnapping and enslavement, against which they had little recourse. Most kidnapped free blacks were forcibly abducted, but other methods, such as luring victims with job offers or falsely claiming free people as fugitive slaves, were used as well. Kidnapping of blacks was actually facil.